An experimental investigation on the collision outcomes of binary liquid metal droplets. (July 2019) - Jia, Xiao; Yang, Juan-Cheng; Zhang, Jie; Ni, Ming-Jiu
Highlights: The present investigation presents a detailed description of the liquid metal GaInSn droplet collision dynamics for the range of 0 ≤ X ≤ 1 and 5 ≤ We ≤ 400, which extends previous experimental liquids and unifies collision outcomes of GaInSn droplets in low and high Weber number range. Six different types of collision outcomes have been observed and the characteristics of these collision regimes are well represented by a series of time-resolved images of the collision event. A new model for the transition between stretching separation and other collision outcomes is presented, which adds the surface tension of the region outside the intersecting region ignored by Ashgriz & Poo (J. Fluid Mech. 221 (1990) 183–204). For head-on collision of GaInSn droplets, spreading diameters in variance with time for different Weber numbers are presented, and the empirical and theoretical relations of maximum dimensionless spreading diameter ξ in variance with We are given. The head-on collision outcomes of coalescence, coalescence after finger and break up after finger for GaInSn droplets are plotted in We-Oh and We/48-Ca map in contrast to the onset of reflexive separation for different liquids. Abstract: Droplet collisions are widely observed either in industrial engineering or in natural phenomena. However, unlike the fully investigated interaction behaviors between water or alkanes droplets, it is still unclear what happens when the droplets are produced of liquid metal, which has larger density and surface tension compared to the common liquids, and hence the collision regimes are expected to be remarkably different from the well-known transition phase maps. In the present study, a series of experiments have been conducted to investigate different collision regimes between binary liquid metal droplets, which are typically of liquid GaInSn, and a wide range of parameter spaces is investigated by covering the Weber number ( We ) from 5 to 400 and the impact parameter ( X ) from 0 to 1, respectively. It turns out that six different collision types are observed, respectively of coalescence, stretching separation, coalescence after finger, separation of finger, breakup after finger and stretching separation with finger pinching, and the transitional borders between them are identified experimentally. Moreover, a theoretical correlation is derived as the upper limit of the transitional curve between stretching separations and other collisions, and by using Ashgriz & Poo's correlation as the lower limit, a transitional region is produced to distinguish stretching separations and other regimes. Particularly, for head-on collision of GaInSn droplets, we also present an empirical and a theoretical correlation for the prediction of dimensionless maximum spreading diameter ( ξ ) in variance with Weber number ( We > 30) within the framework of energy conversion principle. After that, new empirical correlations for the onset of breakup after finger are presented, and the collision outcomes could be divided into surface tension dominated, viscosity dominated, inertia dominated and inertia & viscosity dominated regimes in different regions of the W e / 48 − C a map.